A pathogen imprinted hybrid polymer capacitive sensor for selective Escherichia coli detection. Issue 2 (18th March 2020) - Mugo, Samuel M.; Lu, Weihao; Dhanjai, Dhanjai
Abstract: A versatile pathogen imprinted polymer electrochemical sensor has been developed for Escherichia coli detection. The sensor is based on layer by layer assembly of multi‐walled carbon nanotubes (CNT), nanocellulose (CNC) films, integrated with polyaniline (PANI) doped phenylboronic acid (PBA). The sensing layer is a poly(methacrylic acid) based pathogen microcontact imprinted polymer (PIP). The PIP@PBA/PANI@CNT/CNC sensor exhibits a high affinity towards E. coli in real biological matrices, while effective in discriminating E. coli amidst other bacteria. Using capacitance and impedance as transduction methods, the PIP sensor recorded a low limit of E. coli detection of 8.7 ± 0.5 cfu/ml, with a rapid response of ≤5 min. Abstract : The Escherichia coli imprinted polymer sensor.